TANTANGAN MANAJEMEN BAGI EKSTENTIALISME DI PELAYANAN KESEHATAN - Tjandra, William; Effendi, Rachmat; Ihwanudin, Nandang (Moderation | Journal of Islamic Studies Review, 2022)
The similarity between existentialism and management is that they both deal with human interests. Management and existentialism each have an influence that needs to be analyzed, namely the logic and moral issues of a manager. In this study, we will examine and develop the thoughts of existentialism philosophers with management science to provide critical considerations so that a middle way is obtained in empowering existentialism philosophy in management. In all of these roles, it is argued that a manager's philosophy and value system influence the way he or she performs various managerial tasks. Therefore, management style seems to be directly influenced by certain philosophies, and value systems that direct managers' thinking. Existentialism which sees human nature in its works will be seen as having no identity if the manager's success is only seen in the wealth and money he has but not the ability to produce innovative works in his business. With the philosophy of existentialism, the work of an extentialism manager must show his identity in his work, even though he succeeds or fails, an extentialism manager does not forget himself, his family and the values that build his identity.